Indian child migration in the British Empire - Mukherjee, Sumita (History compass, 2021)
Historical scholarship on the colonial child and of child emigration in the British Empire has flourished in recent years, but the South Asian child migrant has not figured in these studies. Meanwhile, studies on global Indian migration in the British Empire are part of an exciting, growing field, but young people are rarely considered. This article discusses the rich and growing historiography on Indian overseas migration in the 19th and early 20th century and tries to locate the Indian child within it. It surveys work on indentured servitude, labour migration and elite travel and considers how the Indian child migrant can be located in historical works and archives. It argues that the historiography would benefit from an explicit thematisation and historicisation of the Indian child in topics such as ship voyages, child labour and education. In surveying this literature, this article argues that there is huge scope for historians of migration, childhood and empire to examine the experience of children who migrated out from the Indian subcontinent to offer deeper insight into social, economic and political change on a global scale and the Indian child migrant's relationship to shifting ideas of race, class, citizenship and nation in this period.